Implementasi Metode Teorema Bayes Untuk Mendiagnosa Penyakit Pyometra (Infeksi Rahim) Pada Kucing Sphinx - Muhammad Dahria; Hendryan Winata; Zulkifli Lubis (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The continued increase in the number of cat owners is not matched by the relatively small number of veterinarians. Cat owners often can't tell that their cat is sick. The limited time and availability of veterinarians made the delay in handling the cat which resulted in the disease getting worse. Not a few keepers are confused when their cat looks gloomy, weak, and doesn't even know the cat is suffering from pyometra or uterine infection. To be able to solve existing problems, one way that can be done is to use an expert system. The method used is the Bayes Theorem method. The Bayes theorem method is one of the expert system methods that aims to determine the value of certainty in a disease. This study aims to create a computer-based system that can make it easier to diagnose Pyometra disease and can help the Indonesian Cat Association. The results of these problems are in the form of an expert system application to diagnose Pyometra disease in Sphinx cats and get accurate diagnosis results